Larval Gnathostomes and Zoonotic Trematode Metacercariae in Fish from a Local Market in Yangon City, Myanmar - Chai, Jong-Yil (Korean J Parasitol, 2020)
A survey was performed to investigate the infection status of zoonotic helminth larvae in fish from a local market of North Dagon District in Yangon City, Myanmar. A total of 486 fish in 13 species were collected 8 times from December 2015 to December 2019. All fish were transported under ice to a laboratory in Korea and examined for helminth larvae using artificial digestion method. Larval gnathostomes and metacercariae of more than 8 zoonotic trematode species, i.e., Opisthorchis viverrini, Haplorchis taichui, H. pumilio, H. yokogawai, Centrocestus spp., Stellantchasmus falcatus, Pygidiopsis cambodiensis, and Procerovum sp., were detected. Larval gnathostomes were found in 58 (16.0%) out of 362 fish of 6 species, with mean intensity of 2.8 per fish infected. Metacercariae of O. viverrini were detected in 10 (2.9%) out of 349 fish of 5 species, with mean intensity of 16.9 per fish infected. Metacercarial prevalences of 4 intestinal flukes, H. taichui, H. pumilio, H. yokogawai, and Centrocestus spp., were 16.8%, 26.0%, 12.5%, and 15.0% in the positive fish species, respectively, and mean metacercarial intensity was 63.3, 26.8, 86.2, and 8.7 per fish infected. Metacercariae of S. falcatus and P. cambodiensis were detected only from the mullet, Chelon macrolepis. Metacercariae of Procerovum sp. were found in Channa striata and Anabas testudineus. Collectively, it was confirmed that the fish were infected with gnathostome larvae and metacercariae of O. viverrini and intestinal flukes in Yangon City, Myanmar.